The effects of plyometric training on motor skills of top volleyball players - Dragosavljevic, S.; Mitrovic, N.; Stevic, D. (Sports Science and Health, 2019)
The plyometric method is ranked among the most commonly used methods for fitness volleyball training. It leads to the development of explosive strength and reactive velocity of the muscular system based on improving the CNS response and the power required to absorb the stress when landing. The study was of longitudinal type, involving two measurements, an initial measurement for all subjects to determine the initial level of motor ability, and a fi nal measurement where the effects of the experimental program were studied after a programmed experimental process to develop specifi c motor skills of the analyzed sample of subjects. The entire study was conducted on a sample of 72 senior subjects, which were divided into two sub-samples, one sub-sample comprised of the experimental group and the other comprising the control group. The primary objective of the research was to test the infl uence and effect of special treatment of kinesiological activities based on plyometric exercises on the motor skills of the subjects.